Sosialisasi Cara Merawat dan Menyikat Gigi Dengan Benar pada Anak Usia Sekolah di Desa Ungga, Kecamatan Praya Barat Daya, Kabupaten Lombok Tengah - Baiq Ihda Nanda Safriyana; Dina Marlina Oktavia; Alvia Nurani (Universitas Mataram, 2022)
Health maintenance, especially dental and oral health, is an effort to improve health. One of the dental health problems that are very often experienced by the community, especially at the age of children, is dental caries. Awareness of the importance of maintaining dental health from an early age will determine success in maintaining dental and oral health. Early awareness can begin at the age of children. Children aged 6-12 years or school-age children still do not know and understand in maintaining dental and oral hygiene, more intensive care is needed because at that age there is a change of teeth and the growth of new teeth. The purpose of this community service is to increase the understanding of school-age children in maintaining oral and dental hygiene and be able to practice how to brush their teeth properly. The research method is carried out by direct socialization or material exposure. The results obtained indicate that toothbrush socialization can improve understanding in brushing teeth properly in children.